Serum urea: an independent risk factor for cataract - Bhat, Haziqa Bashir; Mufti, Haniyaa; Sajjad, Sheikh (International Journal of Research in Medical Sciences, 2024)
Background: Elevated levels of blood urea/blood urea nitrogen in serum is considered an independent risk factor for the occurrence of cataract. Estimation of these levels can be used as a predictor for the occurrence of cataract. Methods: This was a hospital-based prospective case control study conducted in the department of ophthalmology at SKIMS MCH, Srinagar from January 2023 to June 2023. We evaluated 25 patients admitted for cataract surgery in our department for serum urea and BUN levels and compared their results with 25 age and sex-matched controls admitted for causes other than cataract. The cases with significantly elevated levels of urea were further screened for possible renal impairment using Glomerular filtration rates and urine albumin. Results: 7 out of 25 cases had elevated levels of serum urea with a mean of 44.2±16.19 mg/dl whereas all 25 patients of the control group had normal serum urea levels with a mean of 28.84±4.3 mg/dl. The mean levels of urea were significantly higher in the cases than controls with p<0.0001. 4 out of the 7 patients in the case group with elevated serum urea levels showed impaired glomerular filtration rates and clinically significant levels of urine albumin. Conclusions: The study suggested a statistically significant correlation (p<0.0001) between serum levels of urea and BUN with cataract.